NMG expands NA distribution (Reinforced Plastics, 2016)
Background Supportive nursing practice environments are consistently associated with improved nurse, patient, and organizational outcomes. The American Nurses Credentialing Center's Pathway to Excellence® (Pathway) program is designed to establish and sustain healthy work environments, yet the empirical evidence evaluating its outcomes remains fragmented. Purpose To systematically synthesize quantitative evidence examining the association between Pathway designation or Pathway standards and nurse, patient, and organizational outcomes. Methods A quantitative systematic review was conducted in January 2026 using PubMed, CINAHL, and Embase to identify peer-reviewed studies examining nurse, patient, or organizational outcomes associated with Pathway designation or standards. Risk of bias was independently assessed by two authors using the Joanna Briggs Institute critical appraisal checklists. Results Eight US-based observational studies met the inclusion criteria. Across diverse health care settings, Pathway designation or stronger alignment with Pathway standards was consistently associated with more favorable nurse work environments, lower burnout and intent to leave, stronger engagement in evidence-based practice, higher patient satisfaction, and more positive organizational safety climates. Conclusion The evidence indicates that Pathway designation and standards are positively associated with nurse, patient, and organizational outcomes. Although causal inference is limited, the consistency of findings supports Pathway as a meaningful organizational strategy for strengthening professional nursing practice environments and advancing health care quality.